PERANAN SEKTOR LUAR PERTANIAN TERHADAP KESEMPATAN KERJA DAN PENDAPATAN DI PEDESAAN BERBASIS LAHAN KERING - NURMANAF, A. ROZANY (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 3 November 2006, 2012)
Work opportunity and household income are two important indicators in village economic development. The purpose of analysis focuses in identifying non agricultural sector role on two indicators in dry land village area. Data from Patanas 2004 included six provinces, these are Lampung, West Java, Central Java, East Java, South Sulawesi and West Nusa Tenggara is the main source of information in the analysis. The results show that agricultural sector is dominant source of household income in dry land villages. High proportion in household labor force who are absorbed in agricultural sector affect to their working hours and followed by their income from that sector. Higher in household income level tend to higer in skewness level of their distribution. While, income stability relate to income source domination. In the area where agricultural sector (especially food crops) is the main source income, monthly income proportion fluctuate more. Conversly, in the area where non agricultural sector is the main source of income, monthly income proportion will be distribute and fluctuation level is lower. Non agricultural activity, generally can be done any time a whole the year.
Keywords: work opportunity, household income, non agricultural sector PENDAHULUAN